Development thinking and policies: The way ahead - Gert Rosenthal (CEPAL Review, 1996)
This article takes a long-term view of the evolution of development thinking and policies in Latin America and the Caribbean. It begins by looking at the changes in policy formulation trends, noting that the most abrupt changes of this type occurred, first during the period between the wars, and second, in the early 1980s, and although in both cases changes took place which may be considered as swings of the pendulum or phases in a larger picture, they were nevertheless significant. The author then reviews the economic reforms implemented from the 1980s onwards and highlights their common factors, although these cannot be said to belong to a set paradigm, because of the markedly different ways they were applied in the different countries.